Understanding Muslim Theology in the Works of Shaykh Muhammad Ghazali (KEMANUSIAAN The Asian Journal of Humanities, 2013)
This inquiry explores Shaykh Ghazali's perspective on Muslim belief and change, specifically his views on how faith can sustain commitment to holistic change while assuring a favourable interaction with the intellect, without jeopardising human freedom or the laws and patterns of the universe. This study also examines Ghazali's views on the intimate connection between life and Muslim belief, as well as his ideas on the reformation of theological instruction as an effective means of re-shaping Muslims' intellectual identities and actualising change in contemporary Muslim societies. The study of Ghazali's intellectual analysis of Muslim faith and change is vital to understanding aspects of the current debate on religion, reform and modernity, particularly as he addresses many problems and issues pertaining to the methodology of religious understanding and practice in the context of Muslim life.